PROCEDURE DEVELOPMENT OF PILOT SCALE REVERSE FLOW REACTOR START-UP FOR BENZENE CATALYTIC OXIDATION - Topandi, Abdussalam
Benzene is a group of Volatile Organic Compound (VOC) in the category of aromatic compounds that are carcinogenic which endanger the environment. Catalytic oxidation is the best method of processing VOC in terms of performance, work span, flexibility, and operating costs. The Reverse Flow Reactor (RFR) is one of the catalytic oxidation reactors which is operated in unstable conditions. Pilot-scale RFR start-up procedure is carried out in three start-up methods are air flowing in one-way flow, flowing air with the reverse flow, and flowing air with benzene feeding with the reverse flow. This research was conducted to obtain an optimal pilot scale RFR start-up procedure. The RFR start-up operation procedure can affect the energy requirements needed in the oxidation process of benzene with commercial catalysts 7% CuO / ?-Al2O3. The optimum operating conditions for one-way flow with air feeding are the preheater temperature of 138oC, the catalyst zone temperature of 350oC, and the feed flow rate of 1.75 liters per second. The optimum operating conditions produce a maximum reactor temperature of 138oC, the temperature difference is 23oC, and the time to reach steady state is 190 minutes. The optimum operating condition of reverse flow with air feeding is 35 minutes of switching time. The optimum operating condition produce a maximum reactor temperature of 155.5oC and the time to reach steady state for 225 minutes. Low switching time produce a higher maximum reactor temperature. The method with benzene feeding is carried out by feeding air for 360 minutes with a switching time of 30 minutes. The maximum benzene conversion obtained is 31%.